Impact Assessment of Counselling on Family of Children with Intellectual Disability in Cross River State, Nigeria - Akinwumi, Aderibigbe Samson; Philip, Adeleke Owoade; Ayorinde, Akintoye Oluyemi; Obioma, Ajah Mabel; Emmanuel, Ahueansebhor; Etukudo, Ogunjimi Blessing; Sade, Okoye Joy; Osa, Igbineweka Paul; Ayibeya, Apie Martina; Eunice N, Ajuluchukwu; Bullem, Anthony Godwin; Etta, Bisong Anthony; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
This study examined the impact of counseling on the families of children with intellectual disability (ID) in Cross River State, Nigeria. Three research questions were generated to guide the study while the Ex-post-Facto research design was adopted. A purposive sampling technique was used, and 100 parents of children with ID were selected from the Association for Intellectual and Developmental Disabilities of Nigeria (AIDDN), Cross River State Chapter. These parents have been exposed to psychodynamic counseling in the past. The instrument used for data collection was a structured questionnaire titled “Impact of Counseling on Parents of Children with ID (ICPCID)”. The instrument was validated by three experts, two in special education and one in measurement and evaluation. The reliability coefficient of 0.88 was obtained using Cronbach Alpha. The data collected were analyzed using simple percentages, frequencies, and mean scores. The findings revealed, among others, that counseling has a higher impact on the information needs of parents of children with ID. Counseling has a significant positive impact on the emotional stability of parents of children with ID. Counseling has a significant positive impact on stabilizing families of children with ID. Based on the findings, it was recommended, among others, that the Cross River State Government should establish a department of guidance and counseling under the State Ministry of Education that regularly caters for the counseling needs of parents of children with ID in the state.